Two dimensional computer simulation of plasma immersion ion implantation - Kostov, K. G. [UNESP]; Barroso, J. J.; Ueda, M. (FapUNIFESP (SciELO), 2004)
The biggest advantage of plasma immersion ion implantation (PIII) is the capability of treating objects with irregular geometry without complex manipulation of the target holder. The effectiveness of this approach relies on the uniformity of the incident ion dose. Unfortunately, perfect dose uniformity is usually difficult to achieve when treating samples of complex shape. The problems arise from the non-uniform plasma density and expansion of plasma sheath. A particle-in-cell computer simulation is used to study the time-dependent evolution of the plasma sheath surrounding two-dimensional objects during process of plasma immersion ion implantation. Before starting the implantation phase, steady-state nitrogen plasma is established inside the simulation volume by using ionization of gas precursor with primary electrons. The plasma self-consistently evolves to a non-uniform density distribution, which is used as initial density distribution for the implantation phase. As a result, we can obtain a more realistic description of the plasma sheath expansion and dynamics. Ion current density on the target, average impact energy, and trajectories of the implanted ions were calculated for three geometrical shapes. Large deviations from the uniform dose distribution have been observed for targets with irregular shapes. In addition, effect of secondary electron emission has been included in our simulation and no qualitative modifications to the sheath dynamics have been noticed. However, the energetic secondary electrons change drastically the plasma net balance and also pose significant X-ray hazard. Finally, an axial magnetic field has been added to the calculations and the possibility for magnetic insulation of secondary electrons has been proven.